Case report of myoepithelial carcinoma of maxillary sinus - Liaquat, Ahmad; Riaz, Nabeela; Shah, Arun Kumar (Journal of Chitwan Medical College, 2020)
Myoepithelial carcinoma of the salivary gland is extremely rare malignancy. It may arise either in recurrent or pre existing pleomorphic adenoma or de novo in salivary glands. We herein present the case report of 35 years old male patient who presented to us with myoepithelial carcinoma of minor salivary gland of right maxillary sinus. Right total maxillectomy was done and orbital floor reconstruction was done with titanium mesh.